GENETIC DIVERSITY OF GUAVA (Psidium Guajava L.) IN BALI INDONESIA BASED ON RAPD MARKER - Mayadewi, Ni Nyoman Ari; Rai, I Nyoman; Dwiyani, Rindang; Astarini, Ida Ayu (International Journal of Biosciences and Biotechnology, 2016)
The aim of this study was to investigate genetic diversity and relationship of guava (local name: jambu biji) genotypes grown in Bali, Indonesia, based on Random Amplified Polymorphic DNA (RAPD) markers. Twelve guava cultivars namely Jambu biji ‘Australia’, ‘Bangkok Merah’, ‘Bangkok Putih’, ‘Cokorde’, ‘Dadu 1’, ‘Dadu 2’, ‘Getas Merah’, ‘Kamboja’, ‘Kristal’, ‘Pipit’, ‘Susu’ and ‘Variegata’ were collected from nine Regencies in Bali using survey and explorative method. Ten decamers RAPD primers were employed to distinguish between the 12 cultivars and determine their genetic relationships. A dendogram was constructed using coefficient dissimilarity analysis based on phylogenetic analysis using parsimony (PAUP). The twelve cultivars were grouped into 2 main clusters and five smaller clusters. Variation between genotypes of guava local will be good sources for future crop improvemen.
Keywords: DNA markers; RAPD analysis; guava cultivars